Stereotypes, financial literacy, and confidence: An information provision experiment - Julia Peter; Jana Schuetz (Friedrich Schiller University Jena, Faculty of Economics and Business Administration, 2025)
Financial literacy is an important prerequisite for making informed financial decisions, but it remains low, especially among women and older people. Internalized stereotypes can undermine confidence and subsequently affect behavior in financial matters, leading to suboptimal decisions. This paper investigates how stereotype salience affects confidence in financial literacy. In an information provision experiment, we inform respondents about age or gender differences in numeracy to examine the impact on financial literacy, confidence, hypothetical investment and saving decisions, and demand for information and education. We find that being informed about age differences has no significant effect. In contrast, being informed about gender differences increases the confidence of male respondents through a stereotype boost, while leaving female respondents largely unaffected.
Keywords: C90; D91; G53; I24; J16; 330; survey experiment; numeracy; gender stereotypes; age stereotypes